Islamic Values-integrated Disaster Mitigation Education: A Module Development Study for Pre-Service Early Childhood Teachers - Syarfina Syarfina; Rita Mahriza (Journal of Childhood Development, 2026)
Despite Indonesia’s high disaster risk, disaster mitigation education in early childhood teacher preparation remains largely technocratic, with limited integration of faith-based perspectives that shape learners’ moral reasoning and behavioral responses. Existing studies have predominantly emphasized cognitive preparedness, leaving a gap in pedagogical models that connect disaster knowledge with spiritual and ethical dimensions. This study addresses this gap by developing an Islamic value - integrated disaster mitigation learning module for pre-service early childhood teachers. Using a Research and Development (R&D) approach based on the 4-D model (Define, Design, Develop, Disseminate), the study involved expert validation (content, media, and language) and user-based practicality testing with 32 students in an Early Childhood Islamic Education program in Aceh. The findings indicate that the module achieved a high level of validity (M = 3.75) and practicality (M = 3.72), demonstrating its feasibility and usability in instructional contexts. More importantly, the integration of Islamic values, amanah, ikhtiar, sabr, and tawakkul, functioned not merely as supplementary content but as a pedagogical framework that reorients disaster mitigation learning toward moral responsibility, ecological awareness, and reflective decision-making. Analytically, the study shows that embedding faith-based values transforms disaster education from knowledge transmission into value-driven learning, enabling pre-service teachers to conceptualize disaster preparedness as both a scientific and ethical practice. This research contributes to the field by offering an empirically validated model of faith-integrated disaster education and advancing the discourse on holistic approaches in early childhood teacher preparation. The module provides a practical and scalable resource for integrating spiritual values into disaster mitigation curricula in similar socio-religious contexts.